Pengaruh Stres Kerja, Beban Kerja, terhadap kepuasan Kerja (studi pada medical representatif di Kota Kudus) - Dhania, Dhini Rama (Jurnal Psikologi: PITUTUR, 2010)
With the growth of world trade in products where  competition  is  accompanied  by increasingly stringent targets are so high from the company to its marketing, as well as the marketing  of  drug  company  called  Medical Representative is charged with a high enough target. Therefore this study aims to determine Workload Influence on Job Stress, Job Stress and  Effect  on  Medical  Representative  Job Satisfaction  in  Kudus.  From  the  results  of hypothesis test showed that the adjusted R2 of -, 025 indicates that the effect of workload on job stress at 2.5%. With a very small effect, may imply  that  no  form  of  workload  influence  on work stress. while for the Effect of Work Stress on Job Satisfaction gained 0,033 Adjusted R2 results  show  an  effect  of  work  stress  on  job satisfaction by 3.3%, With very little effect, may imply that no form of the effect of job stress on job satisfaction.